STATUS INDEKS PENCEMARAN PERAIRAN KAWASAN MANGROVE BERDASARKAN PENILAIAN FISIKA-KIMIA DI PESISIR KECAMATAN BREBES JAWA TENGAH - Wisnu Arya Gemilang; Gunardi Kusumah (EnviroScienteae, 2017)
Settlement growth and activity of the population in the Brebes Subdistrict upstream side is also predicted to trigger intrusion and rising sea levels that affect the flow and availability of fresh water needed for the survival of life mangrove vegetation, especially in the adult stage. Therefore, identification of the quality of waters in the mangrove areas is needed to determine the status of these waters pollution index. Measurement of physical and chemical parameters of waters in situ using a Water Quality Checker (DKK TOA WQC Type-24) and laboratory testing of some samples to determine the nutrient content of the water is also performed. Insitu value measurement results later are calculated by using a pollution index refers to the Decree of the State Minister of Environment Number 51 The year 2004 on Guidelines for Determination of Water Quality Status. Index of water pollution Brebes District mangrove area is divided into three criteria: pollution index good condition, lightly polluted and heavily polluted. The section near the front mangrove estuary and enter the index criteria lightly polluted.